Sizing agent for reinforcing fibers, reinforcing fiber, and composite material

A sizing agent with hydrocarbon compounds and nonionic surfactants addresses cohesiveness and fluffing issues in reinforcing fibers, enhancing adhesion and processing efficiency.

JP2024176826AActive Publication Date: 2024-12-19TAKEMOTO OIL & FAT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023095646
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-19
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

Existing sizing agents for reinforcing fibers, such as those described in Japanese Patent Application Laid-open No. 2006-22441, suffer from issues of reduced cohesiveness and fluffing during processing after storage, which affect the adhesion and processing efficiency of fiber materials.

Method used

A sizing agent comprising hydrocarbon compounds like mineral oil and poly-α-olefins, nonionic surfactants, and optionally thermosetting resins is formulated, with specific content ratios to enhance cohesiveness and prevent fluffing, ensuring better adhesion to matrix resins.

Benefits of technology

The proposed sizing agent significantly improves the cohesiveness and processing stability of fiber materials, reducing fluffing and enhancing adhesion to matrix resins, thereby improving the efficiency and quality of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176826000001
    Figure 2024176826000001
  • Figure 2024176826000002
    Figure 2024176826000002
  • Figure 2024176826000003
    Figure 2024176826000003
Patent Text Reader

Abstract

To improve the bundling capability of fiber materials while reducing fuzziness during processing after storage.SOLUTION: A sizing agent for reinforcing fibers contains: one or more hydrocarbon compounds (A) which are selected from mineral oil, liquid paraffin, and poly-α-olefin; and a nonionic surfactant (B). The content of the hydrocarbon compounds (A) in the nonvolatile content is more than 0 mass% and less than 50 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sizing agent for reinforcing fibers, a reinforcing fiber, and a composite material. [Background technology]

[0002] A sizing agent is a chemical applied to fiber materials such as carbon fibers, and is used for the purpose of suppressing damage to the fiber materials, increasing the bundling of the fiber materials, etc. For example, JP 2006-22441 A (Patent Document 1) discloses a sizing agent for carbon fibers containing 50% by mass or more of mineral oil, and a carbon fiber for reinforcing a thermoplastic resin obtained by applying the sizing agent to the carbon fiber. According to the invention described in Patent Document 1, a carbon fiber for reinforcing a thermoplastic resin that has excellent adhesion to thermoplastic resins such as polypropylene, and excellent fiber opening and abrasion resistance can be provided at low cost. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-22441 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the invention described in Patent Document 1 has room for improvement in terms of the bundling ability of the fiber material after the application of the sizing agent. Also, the fiber material to which the sizing agent of Patent Document 1 is applied may become fuzzed when processed after storage.

[0005] Therefore, there is a need for a sizing agent for reinforcing fibers that can increase the bundling ability of fiber materials and suppress fuzzing when they are stored and then processed, as well as for reinforcing fibers and composite materials to which the sizing agent for reinforcing fibers is applied. [Means for solving the problem]

[0006] The present invention First Sizing agents for reinforcing fibers include mineral oil, liquid paraffin, and It is liquid at room temperature The composition contains one or more hydrocarbon compounds (A) selected from poly-alpha-olefins, and a nonionic surfactant (B), and the content of the hydrocarbon compound (A) in the nonvolatile matter is more than 0 mass% and less than 50 mass%. Special It is a sign.

[0007] The second sizing agent for reinforcing fibers according to the present invention is characterized in that it contains a hydrocarbon compound (A) containing at least a mineral oil and a poly-alpha-olefin, and a nonionic surfactant (B), and the content of the hydrocarbon compound (A) in the non-volatile matter is more than 0 mass% and less than 50 mass%.

[0008] The third sizing agent for reinforcing fibers according to the present invention is characterized in that it contains a hydrocarbon compound (A) containing at least a mineral oil having an aromatic content of more than 0 mass% and not more than 5 mass%, and a nonionic surfactant (B), and the content of the hydrocarbon compound (A) in the nonvolatile matter is more than 0 mass% and less than 50 mass%.

[0009] A fourth sizing agent for reinforcing fibers according to the present invention is characterized in that it contains a hydrocarbon compound (A) containing at least a poly-alphaolefin which is a trimer to octamer of 1-decene, and a nonionic surfactant (B), and the content of the hydrocarbon compound (A) in the nonvolatile matter is more than 0 mass% and less than 50 mass%.

[0010] A fifth sizing agent for reinforcing fibers according to the present invention is characterized in that it contains one or more hydrocarbon compounds (A) selected from mineral oil, liquid paraffin, and poly-alpha-olefin, a nonionic surfactant (B), and a resin (C) containing a thermosetting resin (C1) and a polyester resin (C2), and that the content of the hydrocarbon compounds (A) in the nonvolatile matter is more than 0 mass% and less than 50 mass%.

[0011] The reinforcing fiber according to the present invention is Either It is characterized by having a sizing agent for reinforcing fibers attached thereto.

[0012] The composite material according to the present invention is characterized by containing the above-mentioned reinforcing fiber and a matrix resin which is a thermosetting resin.

[0013] These features make it possible to improve the bundling ability of the fiber material and suppress fluffing when the fiber material is processed after storage, compared to the case where a conventional sizing agent is used.

[0014] Preferred embodiments of the present invention will be described below. However, the scope of the present invention is not limited to the preferred embodiments described below.

[0015] In one embodiment, the sizing agent for reinforcing fibers according to the present invention preferably contains an alkylene oxide adduct of an aromatic alcohol (B1) as the nonionic surfactant (B).

[0016] This configuration tends to improve the adhesion of the sized fiber material to the matrix resin.

[0017] In one embodiment, the sizing agent for reinforcing fibers according to the present invention preferably further contains one or more resins (C) selected from a thermosetting resin (C1) and a polyester resin (C2).

[0018] This configuration tends to improve the adhesion of the sized fiber material to the matrix resin.

[0019] In one embodiment, the sizing agent for reinforcing fibers according to the present invention preferably contains a thermosetting resin (C1) as the resin (C).

[0020] This configuration tends to improve the adhesion of the sized fiber material to the matrix resin.

[0021] In one embodiment, the sizing agent for reinforcing fibers according to the present invention preferably contains a thermosetting resin (C1) and a polyester resin (C2) as the resin (C).

[0022] This configuration tends to result in particularly good adhesion of the sized fiber material to the matrix resin.

[0023] In one embodiment, the sizing agent for reinforcing fibers according to the present invention comprises the hydrocarbon compound (A), the nonionic surfactant, sex It is preferable that the proportion of the mass of the hydrocarbon compound (A) is 0.1 mass% or more and less than 50 mass%, the proportion of the mass of the nonionic surfactant (B) is 0.1 mass% or more and 50 mass% or less, and the proportion of the mass of the resin (C) is 20 mass% or more and 90 mass% or less, relative to the total mass of the surfactant (B) and the resin (C).

[0024] This configuration makes it easy to achieve high levels of both the bundling ability of the fiber material and the suppression of fuzzing when it is processed after storage.

[0025] In one embodiment, the reinforcing fiber according to the present invention is preferably an inorganic fiber having the sizing agent for reinforcing fiber attached thereto.

[0026] According to this configuration, the present invention can be easily applied to reinforce composite materials whose base material is resin, ceramic, metal, or the like.

[0027] In one embodiment of the reinforcing fiber according to the present invention, the inorganic fiber is preferably a carbon fiber or a glass fiber.

[0028] This configuration makes the present invention particularly applicable to the reinforcement of composite materials whose matrix is ​​resin, ceramic, metal, or the like.

[0029] Further features and advantages of the present invention will become more apparent from the following description of illustrative and non-limiting embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The embodiment of the sizing agent for reinforcing fibers and reinforcing fibers according to the present invention will be described below. In the following, an example in which the sizing agent for reinforcing fibers according to the present invention (hereinafter simply referred to as "sizing agent") is applied to a sizing treatment of a fiber material will be described.

[0031] [Configuration of sizing agent] The sizing agent according to the present embodiment contains, as non-volatile components, a hydrocarbon compound (A) and a non-ionic surfactant (B). In addition, as a non-volatile component that may be optionally contained in the sizing agent, there is a resin (C).

[0032] (Hydrocarbon compounds) The sizing agent according to this embodiment contains one or more hydrocarbon compounds (A) selected from mineral oil, liquid paraffin, and poly-α-olefin. The hydrocarbon compound (A) is preferably liquid.

[0033] The content of the hydrocarbon compound (A) in the non-volatile content of the sizing agent is more than 0 mass% and less than 50 mass%. The non-volatile content of the sizing agent refers to the components that remain without volatilization after the sizing agent is heated in a hot air dryer at 105°C for 2 hours.

[0034] When the sizing agent contains a mineral oil as the hydrocarbon compound (A), the mineral oil is not particularly limited, and either a paraffinic base oil or a naphthenic base oil can be used. The composition of the mineral oil can be expressed by ring analysis (ndM method). The use of a mineral oil having an aromatic content of more than 0 mass% and 5 mass% or less in ring analysis is preferable in that it is easy to suppress fluffing when the sized fiber material is stored and then processed. The naphthene content in ring analysis can be, for example, 25 mass% or more and 50 mass% or less, but is not limited thereto. The paraffin content in ring analysis can be, for example, 40 mass% or more and 75 mass% or less, but is not limited thereto.

[0035] The kinetic viscosity of mineral oil at 30°C is, for example, 10mm 2 / s or more 180mm 2 / s or less, but is not limited to this.

[0036] When the sizing agent contains liquid paraffin as the hydrocarbon compound (A), the liquid paraffin is not particularly limited. The kinetic viscosity of liquid paraffin at 30° C. is, for example, 5 mm 2 / s or more 120mm 2 / s or less, but is not limited to this.

[0037] When the sizing agent contains a poly-α-olefin as the hydrocarbon compound (A), the poly-α-olefin is not particularly limited. Non-limiting examples of poly-α-olefins include polymers of 1-hexene, 1-octene, 1-decene, 1-dodecene, or 1-tetradecene (i.e., α-olefins having 6 to 14 carbon atoms). The degree of polymerization of the polymer is preferably in a range in which the poly-α-olefin is liquid at room temperature, and may be, for example, 3 to 8. In particular, the sizing agent preferably contains a poly-α-olefin that is a trimer to octamer of 1-decene as the hydrocarbon compound (A).

[0038] The sizing agent preferably contains both a mineral oil and a poly-α-olefin as the hydrocarbon compound (A). In this case, the conditions for the mineral oil and the poly-α-olefin are as described above.

[0039] (Nonionic surfactant) The sizing agent according to this embodiment contains a nonionic surfactant (B). The nonionic surfactant (B) may be any nonionic surfactant commonly used in the art. The nonionic surfactant (B) may be a single type of compound or a mixture of multiple types of compounds.

[0040] The nonionic surfactant (B) may be, for example, an alkylene oxide adduct of a compound having a hydroxyl group. Examples of the compound having a hydroxyl group include aromatic alcohols such as tristyrenated phenol, distyrenated phenol, and bisphenol A, and aliphatic alcohols such as dodecyl alcohol, isododecyl alcohol, tetradecyl alcohol, tridecyl alcohol, secondary dodecyl alcohol, secondary tridecyl alcohol, 2-ethylhexyl alcohol, oleyl alcohol, and isononyl alcohol, and aromatic alcohols are preferred. Examples of alkylene oxides include, but are not limited to, ethylene oxide and propylene oxide. Therefore, the nonionic surfactant (B) may preferably be an alkylene oxide adduct (B1) of an aromatic alcohol.

[0041] In addition, multiple types of alkylene oxides may be used in combination in the nonionic surfactant (B). The number of alkylene oxides added may be, but is not limited to, 6 moles or more and 40 moles or less per mole of the nonionic surfactant (B).

[0042] The nonionic surfactant (B) may be one type of compound or a mixture of multiple types of compounds.

[0043] (resin) The sizing agent according to the present embodiment may further contain a resin (C). The resin (C) is one or more resins selected from a thermosetting resin (C1) and a polyester resin (C2). When the resin (C) contains a thermosetting resin (C1), it is preferable that the resin (C) is easy to impart bundling properties to the fiber material. In addition, when the resin (C) contains both a thermosetting resin (C1) and a polyester resin (C2), it is preferable that the resin (C) is easy to impart bundling properties to the fiber material and is easy to suppress fluffing when the sized fiber material is stored and then processed.

[0044] Examples of the thermosetting resin (C1) include epoxy resins and vinyl ester resins. The epoxy resins may be, for example, the jER (registered trademark) series (jER (registered trademark) 828, jER (registered trademark) 834, jER (registered trademark) 1001, jER (registered trademark) 1002, jER (registered trademark) 1004, etc.) manufactured by Mitsubishi Chemical Corporation, the NPES series (NPES301, NPES302, etc.) manufactured by NANYA PLASTIC CORPORATION, and the Sumiepoxy (registered trademark) series (Sumiepoxy (registered trademark) ELM-434, Sumiepoxy (registered trademark) ELM-100, etc.) manufactured by Sumitomo Chemical Co., Ltd., but are not limited thereto. The vinyl ester resin may be, for example, a reaction product of any of the epoxy resins exemplified above and methacrylic acid. The ratio of the amounts of the reaction substrates when generating the reaction product may be such that the epoxy value of the epoxy resin and the acid value of the methacrylic acid are equal, or one of them is larger. The thermosetting resin (C1) may be one type of compound or a mixture of multiple types of compounds.

[0045] The polyester resin (C2) is a copolymer of a diol monomer and a dicarboxylic acid monomer. Therefore, the polyester resin (C2) has, in its molecule, a diol residue, which is a partial structure derived from a diol monomer (a diol compound or a derivative thereof), and a dicarboxylic acid residue, which is a partial structure derived from a dicarboxylic acid monomer (a dicarboxylic acid or a derivative thereof). The composition of the polyester resin (C2) is specified by the ratio (molar ratio) of the monomers that make up the molecule.

[0046] The diol monomer constituting the polyester resin (C2) may include one or more diol compounds. Examples of the diol compound include, but are not limited to, ethylene glycol, diethylene glycol, bisphenol A, ethylene oxide adduct of bisphenol A (Newpol (registered trademark) BPE series (Newpol (registered trademark) BPE-20, Newpol (registered trademark) BPE-40, Newpol (registered trademark) BPE-100, etc.) manufactured by Sanyo Chemical Industries, Ltd.), and propylene oxide adduct of bisphenol A (Newpol (registered trademark) BP series (Newpol (registered trademark) BP-2P, Newpol (registered trademark) BP-3P, Newpol (registered trademark) BP-5P, etc.) manufactured by Sanyo Chemical Industries, Ltd.).

[0047] The dicarboxylic acid monomer constituting the polyester resin (C2) may include one or more dicarboxylic acid compounds. Examples of the dicarboxylic acid compound include, but are not limited to, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, and 5-sulfoisophthalic acid alkali metal salts (such as sodium salt, potassium salt, and lithium salt).

[0048] Non-limiting examples of polyester resin (C2) include copolymers of diethylene glycol, isophthalic acid, and 5-sulfoisophthalic acid sodium salt, copolymers of ethylene glycol, diethylene glycol, isophthalic acid, terephthalic acid, and 5-sulfoisophthalic acid sodium salt, copolymers of an ethylene oxide adduct of bisphenol A and fumaric acid (in other words, copolymers of bisphenol A, ethylene glycol, and fumaric acid), and copolymers of an ethylene oxide adduct of bisphenol A and maleic acid (in other words, copolymers of bisphenol A, ethylene glycol, and maleic acid). The polyester resin (C2) may be one type of compound or a mixture of multiple types of compounds.

[0049] In the case where the sizing agent contains a resin (C), the hydrocarbon compound (A), the nonionic sex It is preferable that the proportion of the mass of the hydrocarbon compound (A) is 0.1% by mass or more and less than 50% by mass, the proportion of the mass of the nonionic surfactant (B) is 0.1% by mass or more and 50% by mass or less, and the proportion of the mass of the resin (C) is 20% by mass or more and 90% by mass or less, relative to the total mass of the surfactant (B) and the resin (C). When the abundance ratio of each component satisfies the above requirements, it is easy to achieve high levels of both the bundling ability of the fiber material and the suppression of fuzzing when processed after storage.

[0050] (Other Ingredients) The sizing agent according to the present embodiment may contain components other than the hydrocarbon compound (A), the nonionic surfactant (B), and the resin (C). Examples of such other components include, but are not limited to, preservatives, antistatic agents, antioxidants, ultraviolet absorbers, antifoaming agents (such as modified silicones), and resins other than the resin (C).

[0051] In addition, a typical embodiment of the sizing agent used in the sizing treatment of a fiber material is a dilution of the non-volatile components such as the hydrocarbon compound (A) with a diluent (generally referred to as a sizing liquid). Such a diluent is also an example of the other components. Examples of diluents include water (tap water, industrial water, ion-exchanged water, distilled water, etc.), acetone, methyl ethyl ketone, N-methyl-2-pyrrolidone, etc., but are not limited thereto. The concentration of the non-volatile components in the sizing agent in the embodiment in which the non-volatile components are diluted with a diluent is not particularly limited, but may be, for example, 10% by mass or more and 60% by mass or less. As described above, the non-volatile components of the sizing agent refer to the components that remain without volatilization after the sizing agent is heated in a hot air dryer at 105°C for 2 hours, and the concentration refers to the ratio of the mass of the non-volatile components in the sizing agent to the mass of the sizing agent.

[0052] [Method of producing sizing agent] The sizing agent according to the present embodiment can be obtained by mixing the hydrocarbon compound (A), the nonionic surfactant (B), and any other components that may be added by a known method, for example, by adding water to the hydrocarbon compound (A), the nonionic surfactant (B), and any other components that may be added at a temperature between 20° C. and 90° C. over a period of 5 hours while stirring.

[0053] [How to use sizing agent] The sizing agent according to the present embodiment is used in a sizing treatment of a fiber material. The sizing treatment is a treatment for attaching a sizing agent to a fiber material, and the method may be a method generally used in the art for attaching this type of sizing agent to a fiber material. That is, the immersion oiling method, the spray oiling method, the roller oiling method, the guide oiling method, and the like may be adopted. Note that when applying each method, the sizing agent may be appropriately diluted with a diluent such as water.

[0054] The amount of the sizing agent attached to the fiber material is not particularly limited. For example, it is preferable that the amount of the sizing agent attached to the entire fiber material to which the sizing agent is attached is 0.1 mass % to 3 mass %.

[0055] In addition, when the sizing agent according to the present embodiment is applied during the production of reinforcing fibers, reinforcing fibers having the sizing agent attached to the fiber material are obtained. This reinforcing fiber is an example of the reinforcing fiber according to the present invention. The fiber material is preferably an inorganic fiber, and in this case, the reinforcing fiber is an inorganic fiber having the sizing agent attached thereto. In addition, it is more preferable that the inorganic fiber is a carbon fiber or a glass fiber.

[0056] These reinforcing fibers can be used in composite materials whose matrix is ​​resin, ceramic, metal, etc. A composite material characterized by including the above-mentioned reinforcing fibers and a matrix resin that is a thermosetting resin is one embodiment of the present invention.

[0057] Other embodiments As one aspect, the present invention can be a sizing agent comprising one or more hydrocarbon compounds (A) selected from mineral oil, liquid paraffin, and poly-alpha-olefin, and a nonionic surfactant (B), wherein the content of the hydrocarbon compound (A) in the non-volatile matter is greater than 0 mass% and less than 50 mass%.

[0058] In one embodiment, the sizing agent for reinforcing fibers according to the present invention may contain mineral oil and poly-α-olefin as the hydrocarbon compound (A). This configuration makes it easy to achieve both high levels of bundling ability of the fiber material and high levels of suppression of fuzzing when processed after storage.

[0059] In one embodiment, the sizing agent for reinforcing fibers according to the present invention may contain, as the hydrocarbon compound (A), a mineral oil having an aromatic content of more than 0 mass% and not more than 5 mass%. This configuration makes it particularly easy to suppress fluffing when the fiber material is processed after storage.

[0060] In one embodiment, the sizing agent for reinforcing fibers according to the present invention may contain a poly-α-olefin which is a trimer to octamer of 1-decene as the hydrocarbon compound (A). This configuration makes it particularly easy to improve the bundling ability of the fiber material.

[0061] Regarding other configurations, it should be understood that the embodiments disclosed in this specification are illustrative in all respects and that the scope of the present invention is not limited thereto. A person skilled in the art would easily understand that appropriate modifications are possible without departing from the spirit of the present invention. Therefore, other embodiments modified without departing from the spirit of the present invention are naturally included in the scope of the present invention. EXAMPLES

[0062] The present invention will be further described below with reference to examples, but the present invention is not limited to the following examples.

[0063] [Preparation of sizing agent] Sizing agents of Examples 1 to 25 shown in Tables 1 and 2 and Comparative Examples 1 to 3 shown in Table 3 were obtained by the following method.

[0064] (1) Raw material (1-1) Hydrocarbon compound The following hydrocarbon compounds were used. All of the hydrocarbon compounds correspond to the hydrocarbon compound (A) according to the above embodiment. In Tables 1 to 3, the content (unit: mass%) of the hydrocarbon compound (A) in the non-volatile content of the sizing agent is indicated by "R A " column.

[0065] (Hydrocarbon Compound A-1) Contains 1% by mass of aromatics, 29% by mass of naphthenes, and 70% by mass of paraffins, and has a kinematic viscosity of 18mm at 30°C. 2 / s mineral oil.

[0066] (Hydrocarbon Compound A-2) It contains 3% by mass of aromatics, 40% by mass of naphthenes, and 57% by mass of paraffins, and has a kinematic viscosity of 52 mm at 30 °C. 2 / s mineral oil.

[0067] (Hydrocarbon Compound A-3) Contains 0.1% by mass of aromatics, 33% by mass of naphthenes, and 66.9% by mass of paraffins, and has a kinetic viscosity of 50mm at 30°C. 2 / s mineral oil.

[0068] (Hydrocarbon Compound A-4) Contains 1% by mass of aromatics, 34% by mass of naphthenes, and 65% by mass of paraffins, and has a kinematic viscosity of 100 mm at 30 °C. 2 / s mineral oil.

[0069] (Hydrocarbon Compound A-5) It contains 4.5% by mass of aromatics, 43% by mass of naphthenes, and 52.5% by mass of paraffins, and has a kinetic viscosity of 162 mm at 30°C. 2 / s mineral oil.

[0070] (Hydrocarbon Compound A-6) It contains 2.5% by mass of aromatics, 30% by mass of naphthenes, and 67.5% by mass of paraffins, and has a kinetic viscosity of 14mm at 30°C. 2 / s mineral oil.

[0071] (Hydrocarbon Compound A-7) It contains 11% by mass of aromatics, 46% by mass of naphthenes, and 43% by mass of paraffins, and has a kinetic viscosity of 28 mm at 30°C. 2 / s mineral oil.

[0072] (Hydrocarbon Compound A-8) Dynamic viscosity at 30℃ is 6mm 2 / s liquid paraffin.

[0073] (Hydrocarbon Compound A-9) Dynamic viscosity at 30℃ is 18mm 2 / s liquid paraffin.

[0074] (Hydrocarbon Compound A-10) Dynamic viscosity at 30℃ is 35mm 2 / s liquid paraffin.

[0075] (Hydrocarbon Compound A-11) Dynamic viscosity at 30℃ is 60mm 2 / s liquid paraffin.

[0076] (Hydrocarbon Compound A-12) Dynamic viscosity at 30°C is 104mm 2 / s liquid paraffin.

[0077] (Hydrocarbon Compound A-13) Dynamic viscosity at 30°C is 36mm 2 / s, and is a polyalphaolefin mainly composed of 1-decene trimer.

[0078] (Hydrocarbon Compound A-14) Dynamic viscosity at 30°C is 72mm 2 / s, and is a poly-α-olefin mainly composed of trimers to pentamers of 1-decene.

[0079] In addition, poly-α-olefin is a mixture of oligomers with different degrees of polymerization, and the oligomer with the highest abundance ratio (molar basis) is the main component of the poly-α-olefin. For example, hydrocarbon compound A-14 is a poly-α-olefin with the highest abundance ratio of 1-decene trimers. Also, hydrocarbon compound A-15 is a poly-α-olefin with a higher abundance ratio of 1-decene trimers, tetramers, and pentamers than the components with other degrees of polymerization. The abundance ratio of oligomers for each degree of polymerization of poly-α-olefin can be determined, for example, by GC-MS analysis (gas chromatography mass spectrometry).

[0080] (1-2) Non-ionic sex Surfactants The non-ionic sex Surfactants were used. sex The surfactant may also be a nonionic surfactant according to the above embodiment. sex This corresponds to surfactant (B), and among these, nonionic sex Surfactants B1-1 to B1-8 correspond to the alkylene oxide adduct (B1) of aromatic alcohol according to the above embodiment. However, the manufacturing method shown for each nonionic surfactant is only an example, and the results of the examples and comparative examples will not change even if the nonionic surfactant is manufactured by a method other than the method exemplified below.

[0081] (Non-ionic sex Surfactant B1-1) Tristyrenated phenol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:15:9 to obtain a nonionic surfactant B1-1, which is an ethylene oxide-propylene oxide random adduct of tristyrenated phenol.

[0082] (Non-ionic sex Surfactant B1-2) Distyrenated phenol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:20:5 to obtain the nonionic surfactant B1-2, which is a random adduct of distyrenated phenol with ethylene oxide and propylene oxide.

[0083] (Non-ionic sex Surfactant B1-3) Bisphenol A was reacted with ethylene oxide in a molar ratio of 1:18 to obtain a nonionic surfactant B1-3, which is an ethylene oxide adduct of bisphenol A.

[0084] (Non-ionic sex Surfactant B1-4) Bisphenol A was reacted with ethylene oxide in a molar ratio of 1:10 to obtain a nonionic surfactant B1-4, which is an ethylene oxide adduct of bisphenol A.

[0085] (Non-ionic sex Surfactant B1-5) Tristyrenated phenol was reacted with ethylene oxide in a molar ratio of 1:34 to obtain a nonionic surfactant B1-5, which is an ethylene oxide adduct of tristyrenated phenol.

[0086] (Non-ionic sex Surfactant B1-6) Distyrenated phenol was reacted with ethylene oxide in a molar ratio of 1:18 to obtain a nonionic surfactant B1-6, which is an ethylene oxide adduct of distyrenated phenol.

[0087] (Non-ionic sex Surfactant B1-7) Tristyrenated phenol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:12:4 to obtain the nonionic surfactant B1-7, which is an ethylene oxide-propylene oxide random adduct of tristyrenated phenol.

[0088] (Non-ionic sex Surfactant B1-8) Distyrenated phenol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:10:6 to obtain the nonionic surfactant B1-8, which is a random adduct of distyrenated phenol with ethylene oxide and propylene oxide.

[0089] (Nonionic surfactant B-9) Dodecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:7 to obtain a nonionic surfactant B-9, which is an ethylene oxide adduct of dodecyl alcohol.

[0090] (Nonionic surfactant B-10) Isododecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:12 to obtain nonionic surfactant B-10, which is an ethylene oxide adduct of isododecyl alcohol.

[0091] (Nonionic surfactant B-11) Tetradecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:9 to obtain a nonionic surfactant B-11, which is an ethylene oxide adduct of tetradecyl alcohol.

[0092] (Nonionic surfactant B-12) Tridecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:15 to obtain a nonionic surfactant B-12, which is an ethylene oxide adduct of tridecyl alcohol.

[0093] (Nonionic surfactant B-13) Secondary dodecyl alcohol was reacted with ethylene oxide in a molar ratio of 1:12 to obtain nonionic surfactant B-13, which is an ethylene oxide adduct of secondary dodecyl alcohol.

[0094] (Nonionic surfactant B-14) Secondary tridecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:7 to obtain nonionic surfactant B-14, which is an ethylene oxide adduct of secondary tridecyl alcohol.

[0095] (Nonionic surfactant B-15) 2-Ethylhexyl alcohol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:2:6 to obtain the nonionic surfactant B-15, which is a random adduct of ethylene oxide and propylene oxide with 2-ethylhexyl alcohol.

[0096] (Nonionic surfactant B-16) Oleyl alcohol and ethylene oxide were reacted in a molar ratio of 1:15 to obtain a nonionic surfactant B-16, which is an ethylene oxide adduct of oleyl alcohol.

[0097] (Nonionic surfactant B-17) Isononyl alcohol was reacted with ethylene oxide in a molar ratio of 1:10 to obtain a nonionic surfactant B-17, which is an ethylene oxide adduct of isononyl alcohol.

[0098] (1-3) Resin The following resins were used. All of the resins correspond to the resin (C) according to the above embodiment. Furthermore, the resins C1-1 to C1-11 correspond to the thermosetting resin (C1) according to the above embodiment, and the resins C2-1 to C2-5 correspond to the polyester resin (C2) according to the above embodiment.

[0099] (Resin C1-1) The epoxy resin is jER (registered trademark) 828 manufactured by Mitsubishi Chemical Corporation.

[0100] (Resin C1-2) The epoxy resin is jER (registered trademark) 1001 manufactured by Mitsubishi Chemical Corporation.

[0101] (Resin C1-3) The epoxy resin is jER (registered trademark) 1002 manufactured by Mitsubishi Chemical Corporation.

[0102] (Resin C1-4) The epoxy resin is jER (registered trademark) 1004 manufactured by Mitsubishi Chemical Corporation.

[0103] (Resin C1-5) The epoxy resin is NPES301 manufactured by NAN YA PLASTIC CORPORATION.

[0104] (Resin C1-6) The epoxy resin is NPES302 manufactured by NAN YA PLASTIC CORPORATION.

[0105] (Resin C1-7) The epoxy resin is Sumiepoxy (registered trademark) ELM-434 manufactured by Sumitomo Chemical Co., Ltd.

[0106] (Resin C1-8) The epoxy resin is Sumiepoxy (registered trademark) ELM-100 manufactured by Sumitomo Chemical Co., Ltd.

[0107] (Resin C1-9) This vinyl ester resin is obtained by reacting an epoxy resin (jER (registered trademark) 828 manufactured by Mitsubishi Chemical Corporation) with methacrylic acid (MAA manufactured by Mitsubishi Chemical Corporation) in a molar ratio such that the epoxy value of the epoxy resin and the acid value of the methacrylic acid are equimolar.

[0108] (Resin C1-10) This vinyl ester resin is obtained by reacting an epoxy resin (jER (registered trademark) 828 manufactured by Mitsubishi Chemical Corporation) with methacrylic acid (MAA manufactured by Mitsubishi Chemical Corporation) in a ratio such that the epoxy value of the epoxy resin is 15% greater than the acid value of the methacrylic acid.

[0109] (Resin C1-11) This vinyl ester resin is obtained by reacting an epoxy resin (jER (registered trademark) 834 manufactured by Mitsubishi Chemical Corporation) with methacrylic acid (MAA manufactured by Mitsubishi Chemical Corporation) in a molar ratio such that the epoxy value of the epoxy resin and the acid value of the methacrylic acid are equimolar.

[0110] (Resin C2-1) It is a copolymer of diethylene glycol (50 mol%), sodium 5-sulfoisophthalate (4 mol%), and isophthalic acid (46 mol%), and is a polyester resin with a weight average molecular weight of 10,000.

[0111] (Resin C2-2) It is a polyester resin that is a copolymer of ethylene glycol (20 mol%), diethylene glycol (30 mol%), sodium 5-sulfoisophthalate (3 mol%), isophthalic acid (17 mol%), and terephthalic acid (30 mol%), and has a weight average molecular weight of 15,000.

[0112] (Resin C2-3) This polyester resin is obtained by reacting an ethylene oxide adduct of bisphenol A (Newpol (registered trademark) BPE-20 manufactured by Sanyo Chemical Industries, Ltd.) with fumaric acid in a ratio such that the ratio of the hydroxyl value of the ethylene oxide adduct of bisphenol A to the acid value of fumaric acid is 5:4.

[0113] (Resin C2-4) This polyester resin is obtained by reacting an ethylene oxide adduct of bisphenol A (Newpol (registered trademark) BPE-40 manufactured by Sanyo Chemical Industries, Ltd.) with maleic acid in a ratio such that the ratio of the hydroxyl value of the ethylene oxide adduct of bisphenol A to the acid value of fumaric acid is 4:3.

[0114] (Resin C2-5) This polyester resin is obtained by reacting an ethylene oxide adduct of bisphenol A (Newpol (registered trademark) BPE-100 manufactured by Sanyo Chemical Industries, Ltd.) with fumaric acid in a ratio such that the ratio of the hydroxyl value of the ethylene oxide adduct of bisphenol A to the acid value of fumaric acid is 6:5.

[0115] (1-4) Other ingredients The following were used as other components: D-1: Octyl palmitate D-2: Sodium alkylsulfonate with 12 to 15 carbon atoms Diluent: Ion-exchanged water

[0116] (2) Preparation of sizing agent The following raw materials were weighed out: 10 parts by mass of hydrocarbon compound A-1, 5 parts by mass of hydrocarbon compound A-13, 20 parts by mass of nonionic surfactant B1-1, 10 parts by mass of nonionic surfactant B1-2, 40 parts by mass of resin C1-1, and 15 parts by mass of resin C2-1. The weighed raw materials were mixed and stirred at 80° C. while gradually adding 300 parts by mass of ion-exchanged water as a diluent over 5 hours to obtain the sizing agent of Example 1.

[0117] (Examples 2 to 25 and Comparative Examples 1 to 3) Each of the sizing agents of Examples 2 to 25 and Comparative Examples 1 to 3 was obtained in the same manner as in Example 1, except that the raw materials used were those listed in Tables 1 to 3 shown later.

[0118] [Evaluation of sizing agents] Each of the examples and comparative examples was evaluated according to the following procedure. However, carbon fiber and glass fiber were used as fiber materials for evaluating the sizing agent. Both carbon fiber and glass fiber were commercially available fiber materials for resin reinforcement. The type of reinforcing fiber used in the evaluation of each example is shown in the "reinforcing fiber" column of Tables 1 to 3, where carbon fiber is described as "CF" and glass fiber is described as "GF."

[0119] (1) Convergence The sizing agent was applied to a fiber material (carbon fiber or glass fiber) by passing it through a sizing bath filled with the sizing agent of each of the Examples and Comparative Examples. The amount of sizing agent applied was 1.5% based on the weight of the fiber material. The roll of fiber material to which the sizing agent had been applied was set on a creel and unwound at a speed of 5 m per minute, and the state of the fiber material passing through the roller immediately after unwinding was observed. Depending on the observation results, the bundling ability of the fiber material brought about by the sizing agent of each of the Examples and Comparative Examples was evaluated on a three-level scale from A to C. A: Almost no fiber material was found to be wound around the roller, and the passed fiber material was well gathered. B: A small amount of fibrous material was found to be wound around the roller, but the fibrous material that passed through was well held together. C: A large amount of fibrous material was wrapped around the roller, and the fibrous material that passed through was seen to break apart.

[0120] Here, whether or not the fiber material is well-cohered is judged by visual observation based on the criterion of whether or not the fibers are loose enough to leave gaps in the bundle of fiber material.

[0121] (2) Pilling after storage A sizing agent was applied to a fiber material (carbon fiber or glass fiber) having 3000 filaments by passing it through a sizing bath filled with the sizing agent of each of the examples and comparative examples, and the fiber material after the sizing agent was applied was wound on a roll. The amount of the sizing agent applied was 1.5% based on the weight of the fiber material. The wound roll of the fiber material was stored at room temperature for 2 months. The roll of the fiber material after storage was set on a creel and unwound at a speed of 5 m per minute, and the fiber material that passed through the roller immediately after unwound was inserted into the gap of a sponge whose weight was measured in advance so that the contact length was 5 cm, and the generated fluff was attached to the sponge, and the sponge was removed after 15 minutes and the weight was measured, and the weight of the fluff attached to the sponge was measured by taking the difference from the weight measured in advance. In addition, the fiber material after passing through the sponge was subjected to filament winding processing, and its processability was observed. Based on the weight of the fuzz attached to the sponge and the processability of the filament winding process, the effect of the sizing agents of each example in the Examples and Comparative Examples in preventing fuzzing of fiber materials after storage over a period of time was evaluated on a five-level scale from A to E. A: The weight of the fuzz attached to the sponge was less than 10 mg, and the filament winding process proceeded smoothly. B: The weight of the fuzz attached to the sponge was 10 mg or more and less than 20 mg, and the filament winding process proceeded smoothly. C: The weight of the fuzz attached to the sponge was 20 mg or more and less than 30 mg, and the filament winding process proceeded smoothly. D: The weight of the fuzz attached to the sponge was between 30 mg and 50 mg, which was at a level that did not interfere with the operation of the filament winding process. E: The weight of fuzz attached to the sponge was 50 mg or more, and operational problems in the filament winding process were observed.

[0122] (3) Adhesiveness Epoxy resin or vinyl ester resin was used as the matrix resin for evaluating the adhesiveness. When epoxy resin was used, a mixture of epoxy resin (epoxy equivalent 190, jER (registered trademark) 828 manufactured by Mitsubishi Chemical Corporation) and BF3 monoethylamine salt (boron trifluoride monoethylamine manufactured by Stella Chemifa Corporation) in a mass ratio of 100:3 was used as the matrix resin. When vinyl ester resin was used, Lipoxy (registered trademark) R-804B manufactured by Showa Denko K.K., which was cured using a methyl ethyl ketone peroxide curing agent manufactured by Showa Denko K.K., was used as the matrix resin.

[0123] A sizing liquid (non-volatile content concentration 2%) containing the sizing agent of each of the Examples and Comparative Examples was prepared, and a fiber material (carbon fiber or glass fiber) was immersed in the sizing liquid to apply the sizing agent. The amount of the sizing agent applied was 2% based on the weight of the fiber material. A fiber material was taken out from the fiber material to which the sizing agent was applied. Both ends of the fiber material were fixed to a square frame-shaped holder with adhesive so that the fiber material was in a tensed state. A matrix resin was attached to the fiber material as resin droplet-shaped particles with a diameter of about 70 μm. The fiber material was heated for a predetermined time in an air atmosphere at 160° C. to bond the fiber material and the matrix resin to create a test piece. The predetermined time was 90 minutes when the matrix resin was an epoxy resin, and 20 minutes when the matrix resin was a vinyl ester resin. The test piece used for the evaluation of each example was Ma The types of Trix resin are shown in Tables 1 to 3. Ma The information is shown in the "Epoxy Resin" column, where epoxy resin is listed as "EP" and vinyl ester resin is listed as "VE."

[0124] Each sample piece was sandwiched between two blades, which were moved in the fiber axial direction at a speed of 5 mm per minute, and the maximum stress F generated when the resin droplets were peeled off from the fiber material by the blades was measured with a load cell. The interfacial shear strength τ was calculated using the measured value according to formula (1). The calculation of the interfacial shear strength τ (MPa unit) according to the above procedure was performed 20 times for each example of the examples and comparative examples, and the average value was used as the measurement result.

number

[0125] In formula (1), F is the maximum stress (unit: kgf) generated when the resin droplet peels off from the carbon fiber, D is the diameter (unit: mm) of the carbon fiber used as the test piece, and L is the diameter (unit: mm) of the resin droplet in the test piece in the fiber axis direction.

[0126] Based on the obtained interfacial shear strength τ, the adhesion of the sizing agent in each of the Examples and Comparative Examples was evaluated on a four-level scale, A to D. The "reference value" in the following description of each level is 60 MPa when the matrix resin is an epoxy resin, and 40 MPa when the matrix resin is a vinyl ester resin. A: The interfacial shear strength τ is 1.30 times or more the standard value. B: The interfacial shear strength τ is 1.12 times or more and less than 1.30 times the standard value. C: The interfacial shear strength τ is 1.01 to less than 1.12 times the standard value. D: The interfacial shear strength τ is less than 1.01 times the reference value.

[0127] 〔result〕 Tables 1 to 3 show the raw material composition of each of the Examples and Comparative Examples, the fiber materials (carbon fiber or glass fiber) used in the evaluations, and the results of each evaluation.

[0128] Table 1: Evaluation results of sizing agents (Examples) [Table 1]

[0129] Table 2: Evaluation results of sizing agents (Examples) [Table 2]

[0130] Table 3: Evaluation results of sizing agents (comparative examples) [Table 3] [Industrial Applicability]

[0131] The present invention can be used, for example, in the sizing process of textile materials.

Claims

1. One or more hydrocarbon compounds (A) selected from mineral oil, liquid paraffin, and polyalphaolefin; and Contains a nonionic surfactant (B), A sizing agent for reinforcing fibers, characterized in that the content of the hydrocarbon compound (A) in the non-volatile matter is more than 0 mass% and less than 50 mass%.

2. The sizing agent for reinforcing fibers according to claim 1 , comprising a mineral oil and a poly-α-olefin as the hydrocarbon compound (A).

3. 2. The sizing agent for reinforcing fibers according to claim 1, wherein the hydrocarbon compound (A) contains a mineral oil having an aromatic content of more than 0 mass% and not more than 5 mass%.

4. The sizing agent for reinforcing fibers according to claim 1, wherein the hydrocarbon compound (A) contains a poly-α-olefin which is a trimer to octamer of 1-decene.

5. The sizing agent for reinforcing fibers according to claim 1, wherein the nonionic surfactant (B) contains an alkylene oxide adduct of an aromatic alcohol (B1).

6. The sizing agent for reinforcing fibers according to claim 1, further comprising one or more resins (C) selected from a thermosetting resin (C1) and a polyester resin (C2).

7. The sizing agent for reinforcing fibers according to claim 6, wherein the resin (C) comprises a thermosetting resin (C1).

8. The sizing agent for reinforcing fibers according to claim 6, comprising a thermosetting resin (C1) and a polyester resin (C2) as the resin (C).

9. relative to the total mass of the hydrocarbon compound (A), the nonionic surfactant (B), and the resin (C), The proportion of the mass of the hydrocarbon compound (A) is 0.1 mass% or more and less than 50 mass%, The proportion of the mass of the nonionic surfactant (B) is 0.1 mass% or more and 50 mass% or less, and The sizing agent for reinforcing fibers according to claim 6, wherein the mass ratio of the resin (C) is 20 mass% or more and 90 mass% or less.

10. A reinforcing fiber having the sizing agent for reinforcing fibers according to any one of claims 1 to 9 attached thereto.

11. The reinforcing fiber according to claim 10, which is an inorganic fiber to which the sizing agent for reinforcing fibers is attached.

12. The reinforcing fiber according to claim 11, wherein the inorganic fiber is a carbon fiber or a glass fiber.

13. A composite material comprising the reinforcing fiber according to claim 9 and a matrix resin which is a thermosetting resin.

Citation Information

Patent Citations

  • Carbon fiber for reinforcing thermoplastic resin

    JP2006022441A